C-Reactive Protein to Albumin Ratio offers superior risk prediction in patients undergoing mitral valve edge-to-edge repair: a comparison to established surgical risk scores. (3rd October 2022) - Koell, B; Ludwig, S; Weimann, J; Waldschmidt, L; Schirmer, J; Reichenspurner, H; Blankenberg, S; Conradi, L; Schofer, N; Kalbacher, D
Abstract: Background: The population of patients with relevant mitral regurgitation (MR) who stand to gain optimal benefit from mitral valve transcatheter edge-to-edge repair (TEER) remains to be determined. Prior to TEER, a heart-team approach with interdisciplinary decision-making is mandatory integrating both the patient profile and relevant co-morbidities. In addition, the application of established surgical risk scores is recommended by current guidelines. Whether alternative risk prediction is more suitable for this fragile patient cohort burdened with various co-morbidities has not been examined in detail. A simplified approach may be achieved by using the C-Reactive Protein to Albumin Ratio (CAR), but its value in TEER is unclear. Methods: This single-center, retrospective study thought to determine long-term prognostic accuracy of different risk scores in patients with relevant MR undergoing TEER. For this analysis, 316 patients with a median follow-up time of 5.81 years were included. The primary outcome measure was defined as all-cause mortality. ROC analysis was conducted for the identification of the optimal CAR threshold, subsequently dichotomizing patients into two groups (CAR ≤0.4 and CAR >0.4) estimating their long-term event rate using the Kaplan-Meier method. In addition, we evaluated the prognostic value of CAR compared to two conventional surgical risk scores (logistic EuroSCORE and Society of Thoracic Surgeons [STS] risk score) using C-Index analysis. Results: Among 316 high-risk patients undergoing TEER (mean age 75.6±8.2 years, 61.7% male, median logistic EuroSCORE 19.9% [11.7; 31.6], median STS Score 3.8% [2.2; 5.7]), 176 (55.7%) patients had a CAR value ≤0.4. Patients with an elevated CAR (>0.4) predominantly suffered from a higher burden of co-morbidities, such as peripheral artery disease (p=0.001), chronic obstructive pulmonary disease (p=0.044), and chronic kidney disease (p=0.015). Consequently, these patients had significantly higher logistic EuroSCORE and STS Score than patients with CAR ≤0.4 (logistic EuroSCORE p=0.002; STS Score p<0.001). Stratification according to the CAR threshold of 0.4 led to significant differences in the Cumulative Incidence curves (p<0.001). In addition, log-rank test revealed a superior risk stratification of the simplified CAR approach compared to established surgical risk scores (Figure 1). This effect consequently reflects in a higher adjusted C-Index for CAR (0.608) compared to logistic EuroSCORE (0.502; p<0.001) and STS Score (0.498; p<0.001). Conclusions: Our data provide first evidence that alternative risk prediction using CAR allows for a feasible and easy-to-use risk prediction in a real-word TEER cohort presenting with advanced age, a high proportion of frailty and numerous co-morbidities. Alternative risk prediction in TEER patients should be investigated in more detail as the established surgical risk scores seem to demonstrate limited applicability in patients scheduled for TEER. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): University Medical Center Hamburg-Eppendorf, Hamburg, Germany